Data Backup and Recovery Methods in Cloud Computing - Nazir, Danish; Sheheryar, Mir Aman (International Journal of Computer Sciences and Engineering, 2025)
Providing different scenarios of service is the prime bedrock of Cloud computing. Cloud computing offer various services to its associated users. The service offered by cloud depends up on the nature of service subscribed by users associated with it. Storage as-a-service is one of the offered services provided by cloud via internet to its clients. Huge data resides in cloud storage management. To ensure security, cloud shall guarantee that our information is protected in all odds and be accessible whenever need arises. In circumstances like Fire, Flood, Tremors, Technical Snags, Equipment Failure and Coincidental deletion, our data access may be lost. To keep up the effectiveness of the outsourced data there need to be timely implementation of Data Backup involving Recovery Services. This paper provides the comprehensive investigation of different backup methods utilized for Cloud Computing with respect to technical snags and provide the gateways to access shortcomings in cloud backup aspect.